Which Metrics Can I Monitor? Test-Retest Reliability of Countermovement Jump and Countermovement Rebound Jump Force-Time Metrics in Youth Soccer Players In-Season - Andrew Badby; Paul Comfort; Nicholas Ripley; Matthew Cuthbert; Francisco Robles-Palazón; Peter Mundy; John McMahon (International Journal of Strength and Conditioning)
Objective measures provide the most effective means of monitoring the magnitude and time course of changes in neuromuscular function (NMF) resulting from physical activity if measurements are repeatable (reliability). The aim of this study was to determine the test-retest reliability of a range of ratio, outcome, strategy, and kinetic force plate metrics for the countermovement jump (CMJ) and countermovement rebound jump (CMRJ) tests in youth soccer players in the in-season period. A test-retest repeated-measures design was employed consisting of two testing sessions separated by 7-days. In each testing session, male youth soccer players (N = 43; age 17.9 ± 0.9 years, height 181 ± 5.8 cm, body mass 72.5 ± 6.8 kg) from full-time English Football League academies (categories 2 and 4) performed three maximal-effort CMJs and CMRJs in a randomised order on a Hawkin Dynamics Inc. force plate system sampled at 1000 Hz. Fifteen out of 25 CMJ, 11 out of 19 CMJ portion, and five out of 19 rebound jump (RJ) portion metrics demonstrated acceptable absolute (coefficient of variation [CV] ≤10%) and relative (intraclass correlation coefficient [ICC] ≥0.75) reliability for youth soccer players in the in-season period. The CMJ test is a feasible and reliable slow stretch-shortening cycle (SSC) test which can be utilised for monitoring acute changes in NMF in youth soccer players in-season. Practitioners should consider applying a combination of CMJ outcome, strategy, and kinetic metrics in their monitoring processes. The CMRJ test is a less feasible yet reliable fast SSC test which can be utilised for monitoring acute changes in NMF in youth soccer players in-season and can be considered an appropriate alternative to the drop jump (DJ) test as it overcame issues in DJ fall height variability identified in previous research, where acceptable reliability was demonstrated in CMJ portion bodyweight and all outcome metrics.